GRB 130603B: No Compelling Evidence for Neutron Star Merger - Shlomo Dado; Arnon Dar (Advances in Astronomy)
The near infrared (NIR) flare/rebrightening in the afterglow of the short hard gamma ray burst (SHB) 130603B measured with the Hubble Space Telescope (HST) and an alleged late-time X-ray excess were interpreted as possible evidence of a neutron star merger origin of SHBs. However, the X-ray afterglow that was measured with the Swift XRT and Newton XMM has the canonical behaviour of a synchrotron afterglow produced by a highly relativistic jet. The H-band flux observed with HST 9.41 days after burst is that expected from the measured late-time X-ray afterglow. The late-time flare/rebrightening of the NIR-optical afterglow of SHB 130603B could have been produced also by jet collision with an interstellar density bump. Moreover, SHB plus a kilonova can be produced also by the collapse of a compact star (neutron star, strange star, or quark star) to a more compact object due to cooling, loss of angular momentum, or mass accretion.